INITIAL EXPERIENCE OF THORACOSCOPIC LOBECTOMY PERFORMANCE WITH BRONCHOPLASTY - V. G. Pishchik; E. I. Zinchenko; A. I. Kovalenko; A. D. Obornev (Вестник хирургии имени И.И. Грекова)
The article presents an initial Russian experience of video-thoracoscopic bronchoplastic lobectomies performed in 2 clinical cases of centric lung tumors. The upper bronchoplastic lobectomies with right lymphodissection were carried out on two patients in 2012. Complications weren’t observed in intraoperative and postoperative periods. There wasn’t relapse during two years after operation. Thus, the authors came to conclusion that thoracoscopic bronchoplastic lobectomies turned out to be safe and effective interventions in individual patients with centric tumor location, which wasn’t extended outside mouth of the lobar bronchus. The choice of candidates for thoracoscopic bronchoplasty was made using video-bronchoscopy, angio-computer tomography of the thorax and PET. This allowed avoiding an invasive staging and excluded patients with substantial extra-bronchial lesions.